EPIDEMIAS POR ENFERMEDADES INFECTO-CONTAGIOSAS EN EL CINE MEXICANO (1922-2019). - GONZÁLEZ DE ARCE ARZAVE, Rocío Betzabeé; GONZÁLEZ DE ARCE ARZAVE, Julieta Eloisa (Journal of Medicine & Movies / Revista de Medicina y Cine, 2021)
This article reviews 36 Mexican productions or co-productions released between 1922 and 2019 in which they appear, as part of the plot, epidemics due to infectio-contagious diseases. This survey made it possible to detect in Mexican cinema the presence of 15 epidemic diseases of this type: tuberculosis, smallpox, measles, malaria, Spanish influenza, onchocerciasis, poliomyelitis, black fever, diphtheria, black plague, typhoid fever, epidemic cerebrospinal meningitis, rabies, AIDS and an unknown viral flu. The text examines some of the key sequences from these films, and analyzes the way in which these diseases appear in Mexican cinema as allegories that reflect on the social order and that express the collective fears and concerns of a certain historical moment.